Représentations de la vieillesse et orientation professionnelle - Hélène Geurts; Marie-Claire Haelewyck (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
The issues of our exploratory study emerge from a pedagogical observation that students enrolled in the Faculty of Psychology and Educational Sciences (UMONS) have little interest in the options addressing the theme of aging, despite the increasing opportunities. Several theories justify this trend and are frequently associated with the principle of ageism, discrimination based on age criteria (Butler, 1969), widespread in our hypermodern societies (Adam, Joubert & Missotten, 2013).Referring to Abric modeling (1976, 1994, 2005), a questionnaire focusing on the representations of students with regard to old age has been distributed to an occasional sample of 228 subjects of the faculty. Qualitative data were analyzed by a methodological triangulation performed with software NVivo 11 (ACT) and IRaMuTteQ (ADS, CDH, AFC and prototypical analysis).Result's analysis showed a nuanced vision of the elderly carried by students. Indeed, the core of the representation refers to a retired, wise and experienced elder. However, the peripheral areas of the representation would show a more negative view of aging, characterized by losses with handicapping socio-economic consequences, which are wild widespread concerns in our societies. In conclusion, the low orientation towards gerontological professions seems therefore not linked to exclusively negative representations of advancing age, but would also refer to a lack of skills, legitimacy perceived by young people looking for landmarks and recognition. The assumptions will be discussed with practical, teaching and research perspectives to promote socio-professional inclusion.